Multipurpose kitchen tool / Nur Zarifah Iwani Zainal … [et al.] - Zainal, Nur Zarifah Iwani; Othman, Amir Hakim; Mofarizan, Wardina Nabila; Mohd Zubir, Muhammad Afif; Sukur, Noordiana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Cooking is an essential daily activity, but for beginners, it can be daunting due to challenges in accurate ingredient measurement and temperature monitoring. To address these issues, we introduce the Multipurpose Kitchen Tool, a revolutionary device designed to simplify the cooking process. This innovative tool combines the functions of a measuring cup, spoon, thermometer, and weighing scale into one convenient device. Its digital display provides precise readings, ensuring accurate measurements for cooking success. With its practical design and multifunctionality, the Multipurpose Kitchen Tool enhances the cooking experience for both novice and experienced cooks alike. Commercialization of this product offers cost-effectiveness and space optimization, making it an attractive option for various distribution channels including online marketplaces, kitchenware stores, and specialty retailers.